Anaplastic lymphoma kinase (ALK) gene rearrangement in Malaysian patients with lung adenocarcinoma / Noraini Mohamad - Noraini, Mohamad (2017)
The objective of this study is to determine the incidence of ALK gene rearrangement using immunohistochemistry (IHC) in lung adenocarcinoma, which is negative for epidermal growth factor receptor (EGFR) mutation, and to characterize the clinicopathological features of patients with ALK-positive tumours. A total of 120 patients diagnosed with lung adenocarcinoma were selected from 2010 to 2014. Of these, 92 cases were identified as EGFR wild type and considered as suitable candidates for ALK testing utilizing anti-ALK (D5F3) immunohistochemistry (IHC). The reliability of the IHC was confirmed by validating the results against those achieved by fluorescent in-situ hybridization (FISH) to detect ALK gene rearrangements. Twelve (13%) of the 92 cases tested were positive for ALK protein expression using immunohistochemistry. Of these, 7 had tissue available for FISH and all 7 showed ALK rearrangement. In addition, 9 cases previously tested by FISH were negative by both FISH and IHC. There was 100% agreement with respect to ALK re-arrangement/ALK IHC expression, between the two assays, with 9 cases ALK negative by both FISH and immunohistochemistry, and 7 cases ALK positive by both assays. ALK expression showed a significant association with gender, with a higher incidence of ALK positive tumours in female compared to male patients (29.6% versus 6.2%) (OR, 0.156; 95% CI, 0.042-0.575; p=0.005). ALK tumour expression was detected exclusively in patients that had never smoked (0.001) and more frequently in metastatic lesions (22.7%) than in primary tumours (10%) (p=0.047). We conclude that IHC utilising the rabbit monoclonal antibody 05F3 for the detection of ALK expression is a reliable method. It is a more practical way of identifying lung adenocarcinoma patients likely to benefit from treatment with crizotinib targeted therapy.